2018
DOI: 10.1002/jmv.25021
|View full text |Cite
|
Sign up to set email alerts
|

A novel predictor of severe dengue: The aspartate aminotransferase/platelet count ratio index (APRI)

Abstract: To evaluate risk factors for the development of dengue into severe dengue in Guangdong. A retrospective analysis of clinical data from 212 dengue patients between June and October 2014. A total of 174 (82.1%) patients in our study had classic dengue, of which 38 (17.9%) had severe diseases. The frequencies of jaundice, pleural effusion, ascites, and vaginal bleeding were significantly different between the two groups (P < 0.05). The routine laboratory test results for alanine aminotransferase, aspertate aminot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
(30 reference statements)
5
25
0
4
Order By: Relevance
“…These results are more comparable to ours. Another study in China suggests that the ratio between AST/platelet count to be a useful predictor of severe dengue, though this study also was retrospective in nature and data collection was not restricted to early phase of the illness [28]. To have any significant effect on patient management (as prediction of plasma leakage is the goal), it is better to assess early clinical features or laboratory investigations rather than those recorded throughout the entire illness.…”
Section: Discussionmentioning
confidence: 99%
“…These results are more comparable to ours. Another study in China suggests that the ratio between AST/platelet count to be a useful predictor of severe dengue, though this study also was retrospective in nature and data collection was not restricted to early phase of the illness [28]. To have any significant effect on patient management (as prediction of plasma leakage is the goal), it is better to assess early clinical features or laboratory investigations rather than those recorded throughout the entire illness.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic dysfunction and abnormal coagulation are common during the acute stage of dengue infection. About 61%–96% of dengue patients have elevated liver enzyme levels of aspartate aminotransferase (AST) and alanine transaminase (ALT), which peak at around day 7 of the onset of the illness [5, 6], while 7%–42.3% have prolonged activated partial thromboplastin time (aPTT) [5, 7] and 85.8%–98% have thrombocytopenia [8, 9]. Elevated liver transaminases [6, 912], prolonged aPTT [9, 1214] and lower platelet count [4, 8, 9, 12, 13, 15] are more prominent in patients with severe dengue or poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One of these biomarkers, the APRI, has been widely studied as a minimally invasive marker of fibrosis and inflammation in hepatic disease [49, 50]. The APRI has also proven useful in predicting the severity of acute and systemic diseases such as dengue [19] and HELLP syndrome [51]. For this reason, we hypothesized that the APRI is altered in the acute phase of malaria since the liver is also targeted by Plasmodium [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of the clinical value of the APRI in predicting liver inflammation of various etiologies [56]. In a recent and pioneering study on the importance of the APRI as a predictor of signs of dengue severity, the authors concluded that the APRI proved to be an independent and more valuable predictor to discriminate patients with severe forms of the disease than individual changes in hematological and biochemical parameters [19].…”
Section: Discussionmentioning
confidence: 99%